Construction and standardization of dairy cattle management Index - KAPGATE, H G; KAKDE, V G; KULKARNI, S Y (The Indian Journal of Animal Sciences, 2013)
In an attempt to appraise technical know how with which dairymen have entered into dairy enterprise, Dairy Cattle Management Index (DCMI) was precisely developed with prescribed scientific steps.Developed index attained high degree of reliability and validity. The index is likely to be an asset to decide dairy cattle management status of dairy enterpreneur providing further scope for improvement foreconomic benefit.